2022
DOI: 10.3390/jcm11102796
|View full text |Cite
|
Sign up to set email alerts
|

Design and Rationale of the Sevoflurane for Sedation in Acute Respiratory Distress Syndrome (SESAR) Randomized Controlled Trial

Abstract: Preclinical studies have shown that volatile anesthetics may have beneficial effects on injured lungs, and pilot clinical data support improved arterial oxygenation, attenuated inflammation, and decreased lung epithelial injury in patients with acute respiratory distress syndrome (ARDS) receiving inhaled sevoflurane compared to intravenous midazolam. Whether sevoflurane is effective in improving clinical outcomes among patients with ARDS is unknown, and the benefits and risks of inhaled sedation in ARDS requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…However, it was observed that minute ventilation was markedly higher (up to 50%) in the ANA-100 group despite lower pH, which likely resulted in a substantial increase in lung stress and MP [ 27 ]. Whether inhaled sedation devices with lower dead space (e.g., ANA-50) allow lung-protective ventilation in patients with ARDS and improve long-term outcomes is under investigation [ 28 ]. It would be interesting to assess the effects of sedation devices on MP or other variables such as the Costa index in ongoing or future trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was observed that minute ventilation was markedly higher (up to 50%) in the ANA-100 group despite lower pH, which likely resulted in a substantial increase in lung stress and MP [ 27 ]. Whether inhaled sedation devices with lower dead space (e.g., ANA-50) allow lung-protective ventilation in patients with ARDS and improve long-term outcomes is under investigation [ 28 ]. It would be interesting to assess the effects of sedation devices on MP or other variables such as the Costa index in ongoing or future trials.…”
Section: Discussionmentioning
confidence: 99%
“…We used a mouse model of direct lung epithelial injury over multiple days [ 27 , 30 , 31 ] and an in vitro model of alveolar epithelial injury [ 34 , 47 ], which are validated and have translational value. In addition, the sevoflurane concentrations used in our study are similar to those used in clinical practice for deep sedation, which is often required in the early management of clinical ARDS [ 12 , 48 ], and in a large multicenter clinical trial [ 20 ]. Further, a better description of the mechanisms of lung epithelial injury, among other features of ARDS pathogeny, is important to identify endotypes within ARDS (i.e., subgroups with distinct biological or functional features) and to inform the future development of more targeted, endotype-based therapies for ARDS [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane was found to improve gas exchange, reduce alveolar edema, and attenuate pulmonary and systemic inflammation in multiple preclinical models of ARDS [ 10 , 13 17 ], and one pilot randomized controlled trial in patients with ARDS found that sevoflurane, compared to intravenous midazolam, improved arterial oxygenation and decreased alveolar and plasma levels of some inflammatory cytokines and of soluble receptor for advanced glycation end-products (sRAGE), a marker of lung epithelial injury [ 18 ]. Non-randomized evidence suggests potential benefits in patients with ARDS due to COVID-19 [ 19 ], and a large multicenter randomized clinical trial is ongoing to assess the impact of inhaled sedation with sevoflurane on clinical outcomes in patients with ARDS [ 20 ]. However, the precise mechanisms accounting for the lung-protective properties of sevoflurane remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…6 Currently multiple randomized trials are underway to investigate whether inhaled sedation can improve outcomes for patients with acute respiratory distress syndrome (NCT04415060). 33…”
Section: Considerationsmentioning
confidence: 99%